The Cycle of Saint Demetrius in the Patriarchate of Peć - Part II – - Pajić, Sanja (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The initial scenes of the hagiographic cycle of St. Demetrius on the north wall of the naos of the eponymous church in the complex of the Patriarchate of Peć, created in 1322-24, thanks to the atelier of the Greek painter Ioannеs, are followed by frescoes painted during the restoration of 1619/20 by Georgije Mitrofanović, one of the most talented painters of his time. The episodes with Saint Nestor who kills the gladiator Lyaeus in a duel and the martyrdom of Saint Demetrius, preserved legends, have a source in the texts of the Passions of Saint Demetrius. They are separated from the other scenes by red separation lines and belong entirely to the painting from a later period. Certain formal elements reinforce the previously expressed opinion that Mitrofanović used older paintings as a model, although certain changes could have been made. The composition St. Nestor Kills Lyaeus exhibits several peculiarities. Compared to other scenes from the hagiographic cycle, this theme is presented in several iconographic variations, used at the same time. Scholars have expressed an opinion that there are two traditions in portraying the young Christian Nestor who kills the pagan gladiator Lyaeus. The scene with Lyaeus pierced by a spear is considered to be the older iconography, and the younger one, created in the art of the Palaeologus, shows the gladiator killed by throwing him on the mangana. As previously unknown monuments have been published in the meantime, it is possible to suggest a somewhat different typology. Moreover, the presentation of the emperor, as one of the protagonists of the event, must be taken into account in the analysis. Chronologically, the representation of the already ended battle is older, with Nestor over Lyaeus’s body, regardless of whether the gladiator is killed by a spear (the miniature in Theodore Psalter from 1066) or by a spear and on the mangana, while the emperor is watching the spectacle behind the parapet of the lodge (the fresco in the church in Mistras from 1270-85 and on the reliquary from Vatopedi, from the 14th century). In the later version, Lyaeus is lying on the mangana (the damaged fresco in the church of Our Lady of Ljeviš in Prizren from 1309-1313, in Kosovo and Metohija, and in the church of Marko’s Monastery from 1376/77, the Republic of North Macedonia), and the emperor is sitting in an open lodge, alone or accompanied by soldiers and guards. In the miniature of the Menologion of Despot Demetrius Palaiologos (1330-1335), the gladiator is pierced by mangana, but due to the uniqueness of the iconographic solution, it is possible that it presents a special artistic tradition. The extensive damage done to the frescoes in the churches in Kitti (1286) and in Thalames (the end of the 13th century or around 1300) makes the identification of this theme uncertain. The younger and much rarer is the illustration of the moment before Lyaeus falls on the mangana (the fresco in the Visoki Dečani Monastery, Kosovo and Metohija, from around 1337-47/48 and silver tiles from London, 14th century). The fight takes place on a high platform, at the foot of which there are deadly blades, while the bust of the emperor can be seen in a high lodge. A special variant is represented by the scene on silver tiles from London (14th century), which differs from the Dečani fresco by a sword buried in the gladiator’s chest, while the ruling couple is situated in the high lodge. The ruling couple is painted on an icon from Sofia (14th century), but the composition with the duel is lost. On the fresco in the Peć cycle a part of the motif originates from the older tradition, but it has the most similarities with later iconographies in the treatment of Lyaeus (the fresco in Dečani and on London tiles), and the appearance of the high arena with mangana at the foot (the frescoes in Dečani and in Marko’s Monastery, as well as on London tiles). There are no analogies in the preserved scenes for the movement of Nestor, who is holding a long spear with both hands, thrusting it into the body of the enemy, and the broken weapon in Lyaeus’s hand. The same goes for a three-story wooden arena. Although this iconography may be the intervention of Mitrofanović himself, it is more likely that it was created by copying an older fresco by a previous artist - yet it must be emphasized that Maximian’s representation in the lodge with the suite was copied from the scene of Demetrius before Maximian - supported by Ioannеs’s inventiveness shown in painting a church in the Patriarchate of Peć. The Martyrdom of St. Demetrius marks the end of a frieze of scenes on the north wall of the naos. When considering the iconography of this theme, in addition to hagiographic cycles, independent depictions must also be taken into account, most often created as illustrations of the martyrdom of saints in menologion for the date of October 26. According to the accepted opinion for the development of the martyrdom of St. Demetrius, it is believed that the original model with the saint raising his hands in prayer while standing replaced the sitting type, with a transitional variant with hands in prayer, and then with a raised right hand. At the beginning of the 14th century, a new form appeared with the introduction of the representations of the saint’s servant Lupus and the angel bringing the martyr’s crown to Demetrius. However, the views expressed must be reconsidered. There is no doubt that the oldest known iconography depicting a standing figure of the saint (the miniature in the Menologion of Basil II, from around 1000), which was used later with some alterations (the miniature in the cycle of the church calendar in the Menologion from Oxford and the Vatopedi reliquary). The iconography with Demetrius sitting with his right hand raised high appeared earlier than stated by scholars. It is witnessed on a Sinai icon depicting a menologion from the second half of the 11th century. The damage to the frescoes in the Peloponnesian churches in Kitti and in Thalames makes it impossible to iconographical analysis the scene of martyrdom. Preserved examples show that there was a parallel type with Demetrius sitting in two versions, raising his right hand or in a prayer gesture (the fresco in the church in Mistras and the miniature from Demetrius’s life cycle in Menologion in Oxford), or high above his head (the fresco in the Church of Our Lady Ljeviška and as a part of the menologion on the frescoes in the church in Stari Nagoričin from 1315–1317/18, the Republic of North Macedonia; in the narthexes in the church of the Dečani Monastery and the Vlach monastery in Cozia, from around 1391; also on the icon from Sofia and on the money of John V Palaiologos, between 1365–1376). The developed type, with the figures of Lupus and angels, is illustrated in the Thessaloniki Church of the Holy Apostles around 1314, and then on the frescoes (in the church of the Gračanica Monastery in Kosovo and Metohija as a part of the menologion 1318-21 and in the Dečani church as a part of the hagiographic cycle of a saint; also, the remains of the fresco in the parecclesion of St. Demetrius in the monastery Xenophontos on Athos, a second-third quarter of the 14th century) and an icon (from the monastery Great Lavra on Athos, the end of the 14th and early 15th century). Other elements of iconography, such as the number of soldiers carrying out the emperor’s order, which is thought to increase over time, are treated more freely. The building in the background is interpreted as the saint’s basilica in Thessaloniki or the chamber of the public bath, where the event took place. In fact, it is a generally accepted way of marking the area where the martyrdom occurred, in this case copied from an older scene in which St. Demetrius blesses St. Nestor in prison. It can be concluded that the iconographic types did not substitute one another, yet were used simultaneously, although in the final phase of development the sitting type prevailed. The solution found in Peć was well-known in late Byzantine art from where it was taken over by the ateliers of post-Byzantine painters. That Ioannеs used the same pattern we see on the wall of the church in Peć today is indirectly evidenced by the illustration of the same theme, created as a part of the menologion in the narthex of the Patriarchate of Peć complex in 1565. These artists often used the frescoes they encountered as inspiration for their own pictures which is most probably the case with this scene, as well, copied from the original composition from the Church of St. Demetrius in Peć.